Analisis Senyawa Metabolit Primer Pada Jamur Merang (Volvariela volvaceae) Di Daerah Perkebunan Kelapa Sawit Lalundu - Wahidah, Nur; Ratman, Ratman; Ningsih, Purnama (Universitas Tadulako, 2017)
Lalundu region is located in Central Sulawesi where we can find many mushrooms (volvariela volvaceae). The aim of this study is to determine the levels of primary metabolites of mushroom at the regional oil palm plantations Lalundu. The analysis of carbohydrates level was using a UV-vis Spectrophotometer, for protein using a Spectro Direct while for fat by soxhlet. Based on the results of the analysis, the levels of carbohydrates obtained was 7.35% in 1 gram mushroom. The protein content obtained was 1,67% while the fat content results were 2.53%. These indicate that the primary metabolite levels in mushroom at Lalundu region are very high compared to literature.